Fiber-reinforced plastics and gas tanks
Patent Information
- Application Number
- JP2021180993
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-11-05
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-11-05
AI Technical Summary
【0006】 (1)本開示の一形態によれば、繊維強化プラスチックが提供される。この繊維強化プラスチックは、樹脂組成物と、前記樹脂組成物に対する重量比0.5%以上1.0%以下のセルロースナノファイバと、を含有する複合材料と、繊維材料と、を備える。 この形態の繊維強化プラスチックによれば、セルロースナノファイバを備えない場合と比較して、複合材料の気体透過係数を高くすることができる。したがって、高いガス透過性を有する繊維強化プラスチックを得ることができる。 (2)上記形態の繊維強化プラスチックにおいて、前記セルロースナノファイバの平均径が、1nm以上20nm以下であってよい。 この形態の繊維強化プラスチックによれば、セルロースナノファイバの分散性を向上することができる。したがって、ガス透過性のばらつきを低減した繊維強化プラスチックを得ることができる。 (3)上記形態の繊維強化プラスチックにおいて、前記樹脂組成物は、エポキシ樹脂と、酸無水物硬化剤と、エポキシ樹脂硬化促進剤とを含有してよい。 この形態の繊維強化プラスチックによれば、高いガス透過性とともに高い耐水性や耐熱性を有する繊維強化プラスチックを得ることができる。 (4)上記形態の繊維強化プラスチックにおいて、前記樹脂組成物は、前記エポキシ樹脂に対する重量比85%の前記酸無水物硬化剤と、前記エポキシ樹脂に対する重量比3%の前記エポキシ樹脂硬化促進剤とが、前記エポキシ樹脂に含有されてよい。 この形態の繊維強化プラスチックによれば、高いガス透過性とともに高い耐水性や耐熱性を有する繊維強化プラスチックを得ることができる。 (5)本開示の他の形態によれば、ガスタンクが提供される。このガスタンクは、ライナと、前記ライナの外周面上に形成される上記各形態の繊維強化プラスチックを含有する補強層とを備える。 この形態のガスタンクによれば、要求される機械強度が得られるとともに、ガス透過性の高い補強層を有するガスタンクを得ることができる。 本開示は、繊維強化プラスチックやガスタンク以外の種々の形態で実現することも可能である。例えば、繊維強化プラスチックの製造方法やガスタンクの製造方法、繊維強化プラスチックの製造装置、ガスタンクの製造装置等の形態で実現できる。
Smart Images

Figure 0007632237000001 
Figure 0007632237000002 
Figure 0007632237000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a fiber-reinforced plastic and a gas tank using the same. [Background technology]
[0002] A high-pressure tank is known that has a CFRP layer as a fiber-reinforced plastic layer on the outside of the liner to improve strength (for example, Patent Document 1). In this high-pressure tank, gas inside the high-pressure tank permeates the liner, remains in the CFRP layer, and passes through cracks and voids in the CFRP layer to reach the GFRP layer on the outside of the CFRP layer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-085095 A Summary of the Invention [Problem to be solved by the invention]
[0004] In order to prevent gas inside a high-pressure tank from remaining in the fiber-reinforced plastic layer, it is desirable to improve the gas permeability of the fiber-reinforced plastic. [Means for solving the problem]
[0005] The present disclosure can be realized in the following forms. According to one embodiment of the present disclosure, there is provided a fiber reinforced plastic. The fiber reinforced plastic includes a composite material containing a resin composition and cellulose nanofibers at a weight ratio of 0.5% to 1.0% of the resin composition, and a fiber material. The cellulose nanofibers have a diameter of 5 nm, and the resin composition contains an epoxy resin, an acid anhydride curing agent at a weight ratio of 85% of the epoxy resin, and an epoxy resin curing accelerator at a weight ratio of 3% of the epoxy resin. The present disclosure can also be realized in the following forms.
[0006] (1) According to one embodiment of the present disclosure, there is provided a fiber-reinforced plastic, the fiber-reinforced plastic comprising a composite material containing a resin composition and cellulose nanofibers in an amount of 0.5% to 1.0% by weight of the resin composition, and a fiber material. According to this form of fiber-reinforced plastic, the gas permeability coefficient of the composite material can be made higher than that of a composite material not including cellulose nanofibers, and therefore a fiber-reinforced plastic having high gas permeability can be obtained. (2) In the fiber-reinforced plastic of the above embodiment, the average diameter of the cellulose nanofibers may be 1 nm or more and 20 nm or less. According to this type of fiber reinforced plastic, the dispersibility of the cellulose nanofibers can be improved, and therefore, a fiber reinforced plastic with reduced variation in gas permeability can be obtained. (3) In the fiber-reinforced plastic of the above aspect, the resin composition may contain an epoxy resin, an acid anhydride curing agent, and an epoxy resin curing accelerator. According to this form of fiber reinforced plastic, it is possible to obtain a fiber reinforced plastic having high gas permeability as well as high water resistance and heat resistance. (4) In the fiber-reinforced plastic of the above embodiment, the resin composition may contain the acid anhydride curing agent in an amount of 85% by weight relative to the epoxy resin, and the epoxy resin curing accelerator in an amount of 3% by weight relative to the epoxy resin, in the epoxy resin. According to this form of fiber reinforced plastic, it is possible to obtain a fiber reinforced plastic having high gas permeability as well as high water resistance and heat resistance. (5) According to another aspect of the present disclosure, there is provided a gas tank comprising a liner and a reinforcing layer formed on an outer peripheral surface of the liner and containing the fiber-reinforced plastic of any of the above aspects. According to this configuration of gas tank, it is possible to obtain a gas tank having the required mechanical strength and a reinforcing layer with high gas permeability. The present disclosure can be realized in various forms other than fiber reinforced plastics and gas tanks, for example, in the form of a manufacturing method for fiber reinforced plastics, a manufacturing method for gas tanks, a manufacturing device for fiber reinforced plastics, a manufacturing device for gas tanks, etc. [Brief description of the drawings]
[0007] [Figure 1] FIG. 2 is an explanatory diagram showing the configuration of a gas tank. [Diagram 2] 1A to 1C are process diagrams showing a method for producing a fiber-reinforced plastic according to an embodiment of the present invention. [Diagram 3] FIG. 2 is an explanatory diagram showing an example of a composition of a resin composition. [Figure 4] FIG. 2 is an explanatory diagram showing an example of a composition of a composite material. [Diagram 5] 1 is a graph showing the evaluation results of tensile strength as a mechanical property of a composite material. [Figure 6] 1 is a graph showing the evaluation results of breaking elongation as a mechanical property of a composite material. [Figure 7] 1 is a graph showing evaluation results of gas permeability of a composite material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] A. First embodiment: Fig. 1 is an explanatory diagram showing the configuration of a gas tank 100. Fig. 1 shows a schematic external view and a cross-sectional view of the gas tank 100, with the central axis AX of the gas tank 100 as the boundary. The gas tank 100 includes a fiber reinforced resin layer 19 formed using fiber reinforced plastics (FRP) as a first embodiment of the present disclosure.
[0009] The gas tank 100 is a storage container for storing a high-pressure fluid of 10 to 70 MPa, such as hydrogen gas. The gas tank 100 is used, for example, to store hydrogen to be supplied to a fuel cell for a vehicle or a stationary fuel cell. The gas tank 100 may store oxygen, natural gas, or the like in addition to hydrogen gas. The gas tank 100 includes a liner 10, nozzles 16 and 17 disposed on both ends of the liner 10, and a fiber-reinforced resin layer 19 formed on the outer peripheral surfaces of the liner 10 and the nozzles 16 and 17.
[0010] The liner 10 is a container having an internal space for sealing a fluid. The liner 10 is formed of a resin having gas barrier properties, such as nylon, polyamide, ethylene vinyl alcohol copolymer (EVOH), polyethylene, polypropylene, epoxy, polystyrene, etc. The liner 10 includes a cylindrical body 12 and two hemispherical dome portions 14 disposed on both ends of the body 12 along a central axis AX. The liner 10 may be formed of a metal.
[0011] The nozzles 16, 17 are attached to the top of each dome portion 14 of the liner 10 so as to protrude from both ends of the liner 10. The nozzle 16 is made of metal and is used for filling the gas tank 100 with gas or for releasing gas from the gas tank 100. The nozzle 17 is sealed and is used for centering during manufacturing.
[0012] The fiber reinforced resin layer 19 is a reinforcing layer for reinforcing the liner 10. The fiber reinforced resin layer 19 is formed by the fiber reinforced plastic of this embodiment. The fiber reinforced resin layer 19 contains cellulose nanofibers (hereinafter also referred to as "CNF") in order to improve gas permeability. Nanofibers refer to fibers having a width (diameter) of about nanometers, that is, fibers of the so-called nano order. In this embodiment, the fiber reinforced resin layer 19 is formed by winding a bundle of fiber material impregnated with a composite material containing epoxy resin, which is a thermosetting resin, on the surfaces of the liner 10 and the nozzles 16, 17 by a filament winding method and then thermally curing the bundle. However, the fiber reinforced resin layer 19 is not limited to this method, and may be formed, for example, by forming a sheet-like base material using a fiber material, and then impregnating the formed sheet-like base material with the composite material, or by feeding the composite material and the fiber material into an extruder to disperse the fiber material, extruding the molten material into a lump or sheet, and then shaping the sheet into a predetermined shape. Alternatively, the fiber reinforced resin layer 19 may be formed by placing a substrate in which a fiber material is wound around the liner 10 in a mold, and then pressurizing and filling the mold with resin to impregnate the fiber material.
[0013] 2 is a process diagram showing the manufacturing method of the fiber reinforced plastic of this embodiment. In step S10, an epoxy resin, a curing agent, a solvent, a curing catalyst, and CNF are prepared. A general solvent such as water or an organic solvent may be used as the solvent. From the viewpoint of improving dispersibility, the solvent is preferably a polar organic solvent.
[0014] In this embodiment, a bisphenol A type epoxy resin is used as the epoxy resin. However, the epoxy resin is not limited to the bisphenol A type epoxy resin, and any type of epoxy resin may be used, such as a bisphenol F type epoxy resin, a multifunctional epoxy resin, a flexible epoxy resin, a glycidyl ester type epoxy resin, a polymer type epoxy resin, and a biphenyl type epoxy resin. Other examples of epoxy resins include bifunctional glycidyl ether type epoxy resins such as bisphenol S type epoxy resin, hydrogenated bisphenol A type epoxy resin, and biphenyl type epoxy resin, glycidyl ester type epoxy resins such as hexahydrophthalic acid glycidyl ester and dimer acid glycidyl ester, linear aliphatic epoxy resins such as epoxidized polybutadiene and epoxidized soybean oil, heterocyclic epoxy resins such as triglycidyl isocyanurate, and N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenyl methacrylate. Examples of suitable epoxy resins include glycidylamine-type epoxy resins such as glycidylamine, N,N,N',N'-tetraglycidyl-1,3-benzenedi(methanamine), 4-(glycidyloxy)-N,N-diglycidylaniline, and 3-(glycidyloxy)-N,N-diglycidylaniline, phenol novolac-type epoxy resins, cresol novolac-type epoxy resins, biphenyl aralkyl-type epoxy resins, naphthalene aralkyl-type epoxy resins, tetrafunctional naphthalene-type epoxy resins, and polyfunctional glycidyl ether-type epoxy resins such as triphenylmethane-type epoxy resins. The above-mentioned epoxy resins may be used alone or in combination of two or more kinds.
[0015] The resin material contained in the fiber reinforced plastic is not limited to epoxy resin, and may be a thermosetting resin such as a phenol resin, a melamine resin, a urea resin, a polyester resin, or a polyimide resin. If the fiber reinforced plastic has sufficient strength, a thermoplastic resin such as a polyolefin, a polyamide, a polycarbonate, or a polyphenylene sulfide may be used instead of the thermosetting resin.
[0016] As the curing agent, various curing agents such as amine-based, acid anhydride-based, and latent curing agent-based curing agents may be used. In this embodiment, an alicyclic acid anhydride curing agent consisting of methylhexahydrophthalic anhydride is used as the curing agent. The curing agent is not limited to methylhexahydrophthalic anhydride, and for example, alicyclic acid anhydrides such as methyltetrahydrophthalic anhydride and methylhexahydrohymic anhydride may be used. Other examples of the curing agent include aliphatic acid anhydrides such as dodecenyl succinic anhydride, aromatic acid anhydrides such as phthalic anhydride and trimellitic anhydride, bisphenols such as bisphenol A, bisphenol F, and bisphenol S, phenol resins such as phenol-formaldehyde resin, phenol-aralkyl resin, naphthol-aralkyl resin, and phenol-dicyclopentadiene copolymer resin, and organic dihydrazides such as dicyandiamide and adipic acid dihydrazide.
[0017] CNF can be obtained by mechanically crushing cellulose as a raw material. As the raw material, non-wood pulp such as wood pulp, cotton, linter, hemp, bacterial cellulose, parenchymal cell fiber, etc. having cellulose type I, and regenerated cellulose fiber using cellulose type II are used. Cellulose can be mechanically crushed by cutting the pulp to a predetermined length with a beater or refiner, and fibrillating or pulverizing it using, for example, a homogenizer, grinder, impact crusher, bead mill, etc. In this embodiment, the CNF is formed so that the average diameter of the cross section is in the range of 1 nm or more and 20 nm or less in order to increase the dispersibility of the CNF in the composite material. In this embodiment, CNF with a diameter of 5 nm is used as the most suitable condition for dispersibility. In this embodiment, the surface of the CNF is further subjected to an acetylation treatment. The dispersibility of the CNF in the composite material can be further improved by the acetylation treatment. However, the acetylation treatment is not essential and may be omitted. Whether or not the CNF surface is acetylated can be identified by, for example, infrared spectroscopy. In order to determine whether the CNF surface has been acetylated in the manufactured gas tank 100 or fiber reinforced resin layer 19, for example, the fiber reinforced resin layer 19 is separated into a fiber material, a resin material, and CNFs with a strong acid solution, and then infrared spectroscopy is performed on the obtained CNFs. From the viewpoint of reducing or avoiding damage to the CNF surface caused by the strong acid solution, the epoxy resin may be swelled with a polar organic solvent or the like, and then the CNFs may be extracted.
[0018] As the curing catalyst, for example, tertiary amines, imidazoles, phosphorus compounds, etc. may be used. A thermal base generator may be used as the curing catalyst. As the curing catalyst, for example, amines such as tris(dimethylaminomethyl)phenol, dimethylbenzylamine, 1,8-diazabicyclo(5,4,0)undecene and its derivatives, imidazoles such as 2-methylimidazole, 2-ethyl-4-methylimidazole, and 2-phenylimidazole and their derivatives may be used. These may be used alone or in combination of two or more kinds. The curing catalyst may also be called a curing accelerator.
[0019] In step S20, the prepared epoxy resin, curing agent, solvent, and CNF are stirred. A magnetic stirrer, a propeller-type stirring device, a homogenizer, a homomixer, an ultrasonic disperser, or the like can be used for stirring. In step S30, a curing catalyst is further added to the materials being stirred, and stirring is continued. In step S40, the solvent is removed by reducing pressure and heating using a rotary evaporator or the like. As a result, a composite material is produced. In this disclosure, a mixture of a resin and a curing agent is also called a "resin composition," and a mixture of a resin composition and CNF is also called a "composite material." The resin composition may further contain a curing accelerator and a solvent. In this embodiment, the resin composition contains an epoxy resin, an acid anhydride curing agent, and an epoxy resin curing accelerator, as described above.
[0020] In step S50, the composite material thus produced is impregnated into a fiber material. In this embodiment, carbon fiber is used as the fiber material. In addition to carbon fiber, glass fiber, aramid fiber, boron fiber, high-strength polyethylene fiber, poly p-phenylenebenzobisoxazole fiber, etc. may be used as the fiber material, and a combination of a plurality of these types of fibers may also be used. In step S60, the carbon fiber impregnated with the composite material is thermally cured. This completes the production of fiber-reinforced plastic.
[0021] The composition of the fiber reinforced plastic of this embodiment will be described with reference to Fig. 3 and Fig. 4. Fig. 3 is an explanatory diagram showing an example of the composition of a resin composition. As shown in Fig. 3, the resin composition contains 85 grams of acid anhydride curing agent and 3 grams of epoxy resin curing accelerator per 100 grams of epoxy resin. That is, the resin composition contains 85% by weight of acid anhydride curing agent relative to the epoxy resin and 3% by weight of epoxy resin curing accelerator relative to the epoxy resin.
[0022] Fig. 4 is an explanatory diagram showing an example of the composition of a composite material. As shown in Fig. 4, the composite material is formed by adding 0.5 grams or more and 1.0 grams or less of cellulose nanofibers to 100 grams of a resin composition. In other words, the composite material contains 0.5% or more and 1.0% or less of cellulose nanofibers by weight relative to the resin composition.
[0023] The relationship between the amount of CNF added and the mechanical properties of the composite material will be described with reference to Figures 5 to 7. As shown in Figures 5 to 7, in this embodiment, the mechanical properties and gas permeability were evaluated using test samples of the composite material manufactured by the above manufacturing method. The evaluation of the mechanical properties shown in Figure 5 and Figure 6 described later is the evaluation result of a tensile test in accordance with JIS B 7721. The load measuring device used was an LTS-50NB manufactured by Minebea Co., Ltd.
[0024] FIG. 5 is a graph showing the evaluation results of the tensile strength as a mechanical property of the composite material. The horizontal axis of FIG. 5 shows the amount (grams) of CNF added to 100 grams of resin composition, and the vertical axis shows the elastic modulus (MPa). The elastic modulus means the ratio of tensile stress to tensile strain. Each plot of the elastic modulus shown in FIG. 5 shows the average value of the results of multiple evaluations. From the viewpoint of improving the strength of the fiber reinforced resin layer 19, the higher the tensile strength of the composite material, the more preferable it is. FIG. 5 shows the target value BD1 of the elastic modulus required for the composite material in the fiber reinforced plastic used in the gas tank 100. As shown in FIG. 5, the elastic modulus of all evaluation samples exceeds the target value BD1 regardless of the amount of CNF added.
[0025] FIG. 6 is a graph showing the evaluation results of the breaking elongation as a mechanical property of the composite material. The horizontal axis of FIG. 6 shows the amount (grams) of CNF added to 100 grams of the resin composition, and the vertical axis shows the breaking elongation (%). The breaking elongation shown in FIG. 6 is exemplified by the breaking elongation at the upper yield point. The breaking elongation of the composite material is preferably higher from the viewpoint of improving the durability of the fiber reinforced resin layer 19 against the deformation of the gas tank 100 due to the expansion of the gas tank 100. FIG. 6 shows the target value BD2 of the tensile elongation required for the composite material in the fiber reinforced plastic used in the gas tank 100. As shown in FIG. 6, the tensile elongation of all samples exceeds the target value BD2 regardless of the amount of CNF added.
[0026] Figure 7 is a graph showing the evaluation results of the gas permeability of the composite material. The horizontal axis of Figure 7 shows the amount (grams) of CNF added per 100 grams of resin composition, and the vertical axis shows the gas permeability coefficient (cm3·cm / (cm2·sec·cmHg)). The evaluation of gas permeability shown in Figure 7 was performed by a differential pressure method in accordance with JIS K 7126. The measurement device used was a differential pressure gas and vapor permeability measurement device (GTR-30X) manufactured by GTR Tech Co., Ltd. The gas used was dry hydrogen gas, and the differential pressure was set to 1 atm. A gas chromatograph was used as the detector.
[0027] As shown in FIG. 7, the gas permeability coefficient of the composite material sample containing 0.5 grams of CNF was about 1.68 times that of the sample not containing CNF, the gas permeability coefficient of the composite material sample containing 1.0 grams of CNF was about 1.64 times that of the sample not containing CNF, and the gas permeability coefficient of the composite material sample containing 2.0 grams of CNF was about 1.33 times that of the sample not containing CNF. That is, it can be understood that the gas permeability coefficient of the composite material is improved by including CNF. This is presumably due to the fact that the orientation of the molecular chains of the resin material is disturbed by the addition of CNF, for example, the stacking interaction is reduced. The gas permeability coefficient decreases when the amount of CNF added is increased from 1.0 grams to 2.0 grams. This is presumably due to the fact that the CNF is saturated and the molecular motion of the resin material is suppressed.
[0028] As described above, the fiber reinforced plastic of the present embodiment contains a composite material to which cellulose nanofibers are added at a weight ratio of 0.5% to 1.0% based on the resin composition, and a fiber material. Therefore, compared to a case in which cellulose nanofibers are not included, the gas permeability coefficient of the composite material can be increased, and a fiber reinforced plastic with high gas permeability can be obtained.
[0029] According to the fiber reinforced plastic of this embodiment, the average fiber diameter of the cellulose nanofibers is 1 nm or more and 20 nm or less, and therefore, it is possible to obtain a fiber reinforced plastic with improved dispersibility of CNF and reduced variation in gas permeability.
[0030] According to the fiber reinforced plastic of the present embodiment, the resin composition contains an epoxy resin, an acid anhydride curing agent, and an epoxy resin curing accelerator, and therefore, a fiber reinforced plastic having high gas permeability, water resistance, and heat resistance can be obtained.
[0031] According to the fiber reinforced plastic of the present embodiment, the resin composition contains 85% by weight of an acid anhydride curing agent and 3% by weight of an epoxy resin curing accelerator, and therefore a fiber reinforced plastic having high gas permeability, water resistance, and heat resistance can be obtained.
[0032] The gas tank 100 of this embodiment includes the liner 10 and a fiber reinforced resin layer 19 as a reinforcing layer containing the fiber reinforced plastic of this embodiment on the outer peripheral surface of the liner 10. Therefore, it is possible to obtain the gas tank 100 that has the required mechanical strength and has a reinforcing layer with high gas permeability.
[0033] The present disclosure is not limited to the above-mentioned embodiment, and can be realized in various configurations without departing from the spirit of the present disclosure. For example, the technical features in the embodiments corresponding to the technical features in each aspect described in the Summary of the Invention column can be appropriately replaced or combined to solve some or all of the above-mentioned problems or to achieve some or all of the above-mentioned effects. Furthermore, if the technical feature is not described as essential in this specification, it can be appropriately deleted. [Explanation of symbols]
[0034] 10: liner, 12: body portion, 14: dome portion, 16, 17: nozzle, 19: fiber reinforced resin layer, 100: gas tank, AX: central axis
Claims
1. A fiber-reinforced plastic, A composite material containing a resin composition and cellulose nanofibers in a weight ratio of 0.5% to 1.0% based on the resin composition; A fiber material, The diameter of the cellulose nanofiber is 5 nm; The resin composition contains an epoxy resin, an acid anhydride curing agent in an amount of 85% by weight relative to the epoxy resin, and an epoxy resin curing accelerator in an amount of 3% by weight relative to the epoxy resin. Fiber reinforced plastic.
2. A fiber-reinforced plastic as described in claim 1, wherein the surface of the cellulose nanofiber has been subjected to an acetylation treatment.
3. Raina and A reinforcing layer formed on the outer peripheral surface of the liner and containing the fiber reinforced plastic according to claim 1. Gas tank.
4. A liner; A reinforcing layer formed on the outer peripheral surface of the liner and containing the fiber reinforced plastic according to claim 2. Gas tank.
Citation Information
Patent Citations
Production method of cellulose nanofiber-containing epoxy resin composition, reinforced matrix resin and fiber reinforced resin composite
JP2015030829A
Epoxy resin composition, fiber-reinforced composite material and molded product
JP2015036414A
Prepreg laminate
JP2016006131A
Resin composition, fiber-reinforced composite material and molded article
JP2016020446A
Epoxy resin composition, and molding, prepreg and fiber-reinforced plastic prepared therewith
JP2018095675A